2016
DOI: 10.1161/strokeaha.116.013491
|View full text |Cite
|
Sign up to set email alerts
|

Early Rivaroxaban Use After Cardioembolic Stroke May Not Result in Hemorrhagic Transformation

Abstract: Background and Purpose-Early anticoagulation after cardioembolic stroke remains controversial because of the potential for hemorrhagic transformation (HT). We tested the safety and feasibility of initiating rivaroxaban ≤14 days after cardioembolic stroke/transient ischemic attack. Methods-A prospective, open-label study of patients with atrial fibrillation treated with rivaroxaban ≤14 days of transient ischemic attack or ischemic stroke (National Institute of Health Stroke Scale <9). All patients underwent mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 11 publications
3
43
0
2
Order By: Relevance
“…In the RAF study, with enrollment from January 2012 to March 2014, <10% of the patients were treated with non–vitamin K oral anticoagulants (NOACs) 4. Observational studies reported that, if NOACs are started early after an index event, the risk of intracranial bleeding appears to be low 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…In the RAF study, with enrollment from January 2012 to March 2014, <10% of the patients were treated with non–vitamin K oral anticoagulants (NOACs) 4. Observational studies reported that, if NOACs are started early after an index event, the risk of intracranial bleeding appears to be low 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…As advanced age is not a contraindication to the use of rivaroxaban [14], he was treated with this DOAC at the dose of 15 mg/die starting 5 days after the index event, despite the presence of intraventricular bleeding occurred after the thrombolytic therapy for the first event. Our results are even more encouraging given that randomized clinical trials with DOACs have excluded acute ischemic stroke patients, and the safety of DOAC administration soon after an index event has only been addressed by observational, prospective, and non-randomized studies [8][9][10][11][12][13]. In particular, in two prospective studies, the treatment with DOACs was commenced after a mean time of four and five days from the index event and no intracranial bleeding was observed during hospitalization [8,13], suggesting the safety of the early use of DOACs after an ischemic episode.…”
Section: Discussionmentioning
confidence: 71%
“…Based on these data and in consideration of the patient's reduced kidney function, we opted for rivaroxaban 15 mg/die [5,15] despite the presence of intraventricular bleeding and the lack of data on the effects of DOACs in case of such a complication. Moreover, little evidence describes the use of anticoagulation in the presence of HT of ischemic lesions [12]. In a recent prospective study including AF patients treated with rivaroxaban (20 mg in 64% of cases) ≤14 days from TIA or ischemic stroke (NIHSS <9), despite the small sample size (n=60), the magnetic resonance imaging performed at baseline and 7 days after the start of therapy showed that no patient developed sHT of ischemic lesions [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations